Downstream community risks post dam-spillage flooding along the Volta River in Ghana: potential pathogens and public health implications - Grace Semabia Kpeli; Prince Agyirey-Kwakye; Counseller Nutifafa Livingstone; Lillian Teye Cudjoe; Emmanuel Edem Dotse; Ebenezer Nyarko; Ebenezer Zar; Obed Nyarko-Otu; Hubert Kwame Agbogli; Godwin Glilekpeh; Solomon Korankye; Priscilla Essandoh; et al. (PLoS ONE, 2026)
Flooding compromises the microbiological quality of domestic and recreational water sources, increasing exposure to waterborne and opportunistic pathogens in affected communities. Following widespread flooding triggered by the September 2023 controlled spillage of the Akosombo and Kpong dams in Ghana, which led to massive flooding, we assessed the microbial quality of water bodies in communities downstream of the Volta River and associated public and ecosystem health implications. In July 2024, water was collected from multiple source types across four downstream townships (Asutsuare, Aveyime, Battor, and Mepe), including river sections, ponds, puddles, wells, boreholes, and canal-associated sites. Samples were filtered, microbial DNA was extracted, and bacterial community composition was profiled using 16S rRNA gene sequencing, with downstream bioinformatics analyses used to characterize microbial diversity, assess spatial variation across sites, and stratify detected taxa according to ecological origin and public health risk. Sequence data obtained from 17 out of 22 samples revealed communities dominated by Proteobacteria with frequent co-occurrence of Bacteroidetes and Firmicutes. Across all sites, 56 microbial taxa and 118 microorganisms were detected. Community composition varied by location and water source type, with bank and mid-river sites generally exhibiting higher richness than puddles and a canal drain. Thirteen samples contained site-specific taxa, indicating marked spatial heterogeneity within and between communities. Microorganisms of public health relevance were frequently detected, including enteric-associated bacteria such as Escherichia coli, Salmonella enterica, Shigella species , and Cronobacter sakazakii , as well as opportunistic and healthcare-associated bacteria including Acinetobacter baumannii , Klebsiella pneumoniae , Pseudomonas aeruginosa , and Stenotrophomonas maltophilia . Higher-risk organisms were most widely distributed in Mepe and Battor, including in groundwater-associated sources. These findings provide molecular evidence of persistent, spatially heterogeneous microbial hazards months after flooding, underscoring continued exposure risks in downstream communities and the need for targeted water safety interventions and risk-informed public health responses.